The prevalence of sight impairment registration post-stroke. (3rd April 2021) - Budd, Alysha; Mather, Faye; Gavin, Nicola; MacDiarmid, Sonia
ABSTRACT: Many stroke survivors are eligible for sight impairment (SI) registration from a chronic visual impairment (VI). The literature and clinical experience show that some individuals who meet the criteria for registration either decline or are not offered registration. The aim of this Orthoptic stroke service review is to determine the reason for declining and whether the individuals feel supported without registration and to recommend service changes to improve the certification process. A service evaluation of stroke survivors who had declined SI registration was undertaken. All those with a diagnosis of stroke, a full Orthoptic assessment, a period of monitoring and were discharged between September 2017 and August 2019 were identified. . Fifty-four stroke survivors were eligible to be registered SI at their last appointment; 31 (57%) were not offered registration for reasons including end of life care. Of the remaining 23s, 14 proceeded with SI registration and nine declined. Four who declined were excluded (44%), as two were registered at a subsequent ophthalmology appointment, two were inappropriate to contact. A telephone interview was undertaken with the remaining five individuals. Of the five stroke survivors that were contacted, three (60%) recalled declining SI registration at their last appointment. All felt they were given enough information to aid their decision. Reasons given for declining registration included not accepting the VI, hoping for recovery and having enough support. The individuals felt they were still able to access services and were happy to remain unregistered. The remaining two stroke survivors could not recall being offered SI registration and subsequently requested to be registered following the telephone call. Of those individuals who initially declined registration, two (40%) decided to proceed with registration following the telephone interview. Although numbers are small it is worth considering a post discharge telephone consultation to stroke survivors who decline registration.